Die Sprache Deutsche Erstausgabe - Bloomfield, Leonard (Edition Praesens, 2001)
Leonard Bloomfield's "Language" (1933) is one of the most important books on linguistics and it is also one of the most frequently quoted. It is very unusual that a scientific book that has been on the market for 67 years has not become outdated. Unbelievably enough, it has never been translated into German, although Bloomfield spoke German like his mother-tongue. His family came from Austria an he specialized in Germanic linguistics. This edition of ,Language" aims to fill this gap and furthermore tries to reflect Bloomfield's ideas in the light of modem linguistics. Therefore it is not a mere translation but a commentated reader , of Bloomfield's ,,Language" and a scientific publication in its own right.